A Comparison of the Effects of 45‐minute Aerobic Training and Cognitive Task Solving on Transient Mood States in a Female Student Sample. Issue 3 (11th June 2019) - Stolarska, Barbara; Stolarski, Maciej; Matthews, Gerald
Abstract : Background: The beneficial effects of moderate‐intensity physical exercise on mood are well established. Students in higher education are a group vulnerable to stress who may benefit from aerobic exercise classes. The present study broadens existing findings by testing the impact on mood of a 45‐minute‐long aerobic training session, conducted in a naturalistic setting. Method: A three‐dimensional mood assessment that distinguished hedonic tone (pleasantness of mood) from energetic and tense arousal dimensions was used for assessment of pre‐ and post‐training mood in a sample of women ( n  =   120) taking part in a 45‐minute aerobic training. A control group ( n  =   120) performed cognitive tasks. Results: Physical but not cognitive activity elevated mood on all three dimensions, but the effect size was largest for energetic arousal. It was also found that mood improvements in terms of energy and tension change were strongest for individuals initially low in hedonic tone. Conclusions: The finding supports the hypothesis that successful completion of an exercise session in a naturalistic setting may enhance mood in female students. At a practical level, the study suggests that exercise classes may help students cope with the mood impairments resulting from demanding cognitive activities, leading to potential educational benefits.